High-Performance Liquid Chromatography in the Black Sea (29/03/2019) - Station 307 - Ricour, Florian; Capet, Arthur (PANGAEA, 2021)
Within the frame of a study on the deep chlorophyll maximum in the Black Sea, water samples were collected conjointly to the deployment of a new Biogeochemical-Argo float (WMO 6903240). The sampling took place onboard the R/V Akademik (Bulgarian Academy of Sciences – Institute of Oceanology) in the western Black Sea (station 307, 43.16°N and 29°E) on March 29, 2018. Water samples were obtained using a CTD carousel with twelve 5 L Niskin bottles. Samples were taken at 12 different depths between the surface and 1000 meters, and were considered to be co-located in time and space with the float deployment. Seawater samples were vacuum filtered through 47 mm diameter Whatman GF/F glass fibre filters (0.7 micrometer pore size). After filtration, filters were stored in liquid nitrogen and kept at -80°C before being analyzed by High-Performance Liquid Chromatography (HPLC). HPLC analyses allow the determination of pigments and by extension the chlorophyll a (chl a) with the best known precision. Using this information on chl a, our objective was to validate, using chl a concentrations derived with HPLC, an algorithm that correct the chl a fluorescence measured by Biogeochemical-Argo floats in the Black Sea by removing the contamination due to the fluorescence of dissolved organic matter.
Keywords: Black Sea; HPLC